2017
DOI: 10.1155/2017/3896539
|View full text |Cite
|
Sign up to set email alerts
|

Lipodystrophy among HIV-Infected Patients Attending Care and Treatment Clinics in Dar es Salaam

Abstract: Background HIV infection and long-term HAART use are associated with metabolic and morphological changes. We assessed prevalence, types, and risk factors associated with lipodystrophy among HIV-infected adults attending CTC in Dar es Salaam, Tanzania. Methods Analysis included 466 HIV-infected patients. Study protocol involved administration of structured questionnaire to collect sociodemographic and clinical information. Diagnosis of lipodystrophy was based on physician clinical assessment. Results Lipodystro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
(42 reference statements)
1
6
1
Order By: Relevance
“…This occurs due to several factors, such as: HIV infection, genetic factors, use of antiretrovirals, among others [12] HIV infection and HAART have been associated with the development of cardiovascular and metabolic complications, including lipodystrophy syndrome. In Brazil, the prevalence of lipodystrophy manifestation has ranged from 32.4 to 64%, in line with the average found in the literature, of 42% (SESSP, 2017), with an overall prevalence of at least one physical abnormality that is related to the poor distribution of body fat, estimated at about 50% after one year of TARV use [13] with an impact on financial life, social relationships, and love relationships [7].…”
Section: Introductionsupporting
confidence: 79%
“…This occurs due to several factors, such as: HIV infection, genetic factors, use of antiretrovirals, among others [12] HIV infection and HAART have been associated with the development of cardiovascular and metabolic complications, including lipodystrophy syndrome. In Brazil, the prevalence of lipodystrophy manifestation has ranged from 32.4 to 64%, in line with the average found in the literature, of 42% (SESSP, 2017), with an overall prevalence of at least one physical abnormality that is related to the poor distribution of body fat, estimated at about 50% after one year of TARV use [13] with an impact on financial life, social relationships, and love relationships [7].…”
Section: Introductionsupporting
confidence: 79%
“…In this study, the prevalence of central obesity was 71.7% (95% CI: 67%–76.4%). This finding is higher than those in studies conducted elsewhere, for instance, 4% in the United States [ 10 ], 12.6% in Tanzania [ 11 ], 36.5% in Malaysia [ 12 ], and 45.7% in Brazil [ 13 ]. This discrepancy may be due to the type used to measure central obesity and sample size variation, in which the current study utilized a large sample size and WHR, which early detected central obesity among HIV-infected population.…”
Section: Discussioncontrasting
confidence: 57%
“…HIV-infected patients had more abdominal visceral fat than extremity fat and demonstrated a higher waist-to-hip ratio (WHR) compared to the control population [ 7 – 9 ]. Similar to the general population, the prevalence of central obesity (the localized accumulation of adipose tissue in the abdomen irrespective of proportion to total body fat) is increasing among HIV-infected persons, for instance, 4% in the United States [ 10 ], 12.6% in Tanzania [ 11 ], 36.5% in Malaysia [ 12 ], and 45.7% in Brazil [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The audience insights also suggested that the fear is associated with the desire to belong and concerns over loss of control that can result from being discriminated against by community members upon testing positive. These concerns are supported by studies that have described the lack of control PLHIV, including men, experience over physical changes, such as lipodystrophy, that serve as clinical manifestations of HIV and make the disease visible as a potential source for stigma and social withdrawal ( Alexias et al, 2016 ; Carr, 2014 ; Gagnon & Holmes, 2012 ; Njelekela et al, 2017 ; Nyamaruze & Govender, 2020 ; Nzuza et al, 2017 ). Other studies have also reported on the stigma, discrimination, and isolation that PLHIV experience ( Gilbert & Walker, 2010 ; Maman et al, 2002 , 2009 ; Mbonu et al, 2009 ; Mlay et al, 2008 ; Roura et al, 2009 ; Wingood et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%